Examining relational digital transformation through the unfolding of local practices of the Finnish taxi industry - Lanamäki, Arto; Väyrynen, Karin; Laari-Salmela, Sari; Kinnula, Marianne (Elsevier, 2020)
Digital transformation has become a central construct in information systems (IS) research. Current conceptualizations largely attribute transformation to intentionality, focus on transformation within a single organization, or assign technology the role of a disruptive agent of change. Likewise, “digital” tends to be a general category of technology, rather than a specific technology enacted in a time and place. Inspired by Schatzkian practice theory and its site ontology, we suggest a contextual viewpoint on digital transformation and call it “relational digital transformation.” We analyzed the change dynamics in the context of taxi dispatch practice in Finland, studying the changing taxi dispatch platforms over years. We investigated five powerful industry actors: two incumbents, two entrants, and a federation of taxi entrepreneurs. We identified events of change in the material arrangements in sites and explain the changes through the process dynamics in the focal practice. We define relational digital transformation as a process through which practice-arrangement bundles of digital technologies evolve over time. This approach assumes the default nature of an industry is to be found in the changing relations between entities rather than in entities themselves. This provides a theoretical extension to the prevailing views of digital transformation in IS literature. It enables studying digital transformation in retrospect without attributing change agency to any entities or technologies a priori. We also contribute to practice-theoretical IS literature by demonstrating how the applicability of practice theoretical analysis extends beyond microphenomena to larger industry-level changes.
Keywords: Contextual explanation; Digital platforms; Digital transformation; Mobile apps; practice theory; Taxi industry; fi=Viestintätieteet|en=Communication Studies|